Numerical Simulation of Centrifugal Pump Cavitation Based on ANSYS. Issue 1 (1st March 2023) - Dong, Jie; Li, Wei
Abstract: Centrifugal pump is the key equipment in petrochemical, agriculture, shipbuilding and other industries. Its safe, reliable and reliable work is an important guarantee to ensure its normal operation. Cavitation is a kind of unsteady compressible turbulent flow, which has a great influence on its performance and efficiency due to material exchange between gas and liquid phases. The appearance of the impeller internal cavitation phenomenon will reduce the pump head and efficiency, which is caused by the impeller and other flow components of damage, causing greater noise, and thereby the pump work and work performance have been greatly affected. Improving the efficiency of the centrifugal pump will undoubtedly reduce the social requirements for energy, which is consistent with the current goal of energy conservation and emission reduction advocated by society. The performance and efficiency of a centrifugal pump can be improved effectively by numerical simulation and analysis of the cavitation phenomenon.